Development of National Technology Audit Policy - Subiyanto Subiyanto (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2017)
The Laws have mandated implementation of technology audit, nevertheless such implementation needs an additional policy that is more technical. The concept of national audit technology policy shall make technology audit as a tool to ensure the benefit of technology application for society and technology advance for nation independency. This article discusses on technology audit policy concept especially infrastructure requirement, with emphasis on regulation, implementation tools, and related institution. The development of technology audit policy for national interest requires provision of mandatory audit implementation, accompanied by tools for developing technology auditor’s competence and technology audit institutional’s mechanism. To guide technology auditor’s competence, concept of national audit technology policy shall classify object of technology audit into product technology, production technology, and management of technology, accompanied by related parameters of technology performance evaluation.